2000
DOI: 10.1086/303112
|View full text |Cite
|
Sign up to set email alerts
|

Intraracial Diversity and Relations among African‐Americans: Closeness among Black Students at a Predominantly White University

Abstract: A case study of black college students at a predominantly white liberal arts college is employed to question continuing assumptions in sociological research that blacks represent social, cultural, and economic homogeneity and that intraracial relations are close and without conflict. The article examines the extent to which black students feel close to other black students on campus, rely on one another for need satisfaction and social interaction, and share similar values, experiences, and attitudes. The auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 22 publications
4
61
0
Order By: Relevance
“…[because the] chance of a black person finding another black person with whom he is compatible is more limited '' (1972:16); they also report ''feelings of disgruntlement due to an insufficient range of personalities with whom to interact '' (1972:19;see also Berry, 1983). In a recent study based on survey data and in-depth interviews of black students in a predominantly white institution, Smith and Moore (2000) report high tensions among black students, particularly around issues such as dating, though the authors also report heterogeneity in how black students respond to their environment. The social duress students experience is hypothesized to reduce chances of graduation.…”
Section: Social Mismatchmentioning
confidence: 99%
See 1 more Smart Citation
“…[because the] chance of a black person finding another black person with whom he is compatible is more limited '' (1972:16); they also report ''feelings of disgruntlement due to an insufficient range of personalities with whom to interact '' (1972:19;see also Berry, 1983). In a recent study based on survey data and in-depth interviews of black students in a predominantly white institution, Smith and Moore (2000) report high tensions among black students, particularly around issues such as dating, though the authors also report heterogeneity in how black students respond to their environment. The social duress students experience is hypothesized to reduce chances of graduation.…”
Section: Social Mismatchmentioning
confidence: 99%
“…Some researchers have focused on the social life of blacks in predominantly white schools (Allen, 1988;Epps, 1972;Hemmons, 1982;Nettles, 1988a,b;Smith, 1981;Smith and Allen, 1984;Smith and Moore, 2000;Thomas, 1981c;Willie and McCord, 1972;Willie and Cunnigen, 1981). After interviewing black students at predominantly white colleges, Willie and McCord (1972) report that ''dating is a serious problem.…”
Section: Social Mismatchmentioning
confidence: 99%
“…Various studies show that students segregate themselves according to race and ethnicity (Lewis 2000;Smith and Moore 2000;Antonio 2001;Villalpando 2003;Li 2008;Stearns et al 2009;Koehler and Skvoret 2010). Smith and Moore (2000) found that segregation occurred even when the opportunity for interracial contact in the form of allocating students to tables with their housemates in the dining halls had been created.…”
Section: Integration Of Diverse Students At University Residencesmentioning
confidence: 99%
“…Smith and Moore (2000) found that segregation occurred even when the opportunity for interracial contact in the form of allocating students to tables with their housemates in the dining halls had been created. Some black students perceived their time in the dining hall as an opportunity to bond and interact with other black students.…”
Section: Integration Of Diverse Students At University Residencesmentioning
confidence: 99%
See 1 more Smart Citation